Ethnobotanical Study of Medicinal Plants for Diabetes Mellitus in the Sanggabuana Area, Karawang, West Java - Putra, Adhiya Nabhan Kusuma; Qotrunnada, Ananda; Wahyudin, Ichsan; Friscilla, Sulastri; Rahayu, Sri Endarti; Putri, Adelia Hasna Trisna (Journal of Tropical Biodiversity, 2023)
Indonesia is the second richest country in terms of biodiversity, particularly in plant species. Generally, the community utilizes plants for traditional medicinal purposes, which is the essence of the field of Ethnobotany. This research aims to identify plants with the highest Use Value (UV) and Fidelity Level (FL) in the local community for treating Diabetes Mellitus (DM). The study was conducted in the Sanggabuana Conservation Foundation area, Karawang, West Java. The methodology involved field observation, interviews, plant identification, and documentation of medicinal plants and residents during interviews. The research revealed that plants with the highest Use Value (UV) were Solanum torvum (tekokak) and Physalis angulata (ciplukan) at 5.26%. The plant with the highest Fidelity Level (FL) for treating Diabetes mellitus was Moringa oleifera (kelor) with a value of 10.53%. Moringa oleifera can be used as a medicinal plant for Diabetes mellitus due to its phytochemical content, such as flavonoids that function as antidiabetics. The parts of the moringa plant used are the leaves, and the processing method involves boiling.